A minimal mechanistic model of plant responses to oxygen deficit during waterlogging - Silou Chen; Hugo J. de Boer; Kirsten ten Tusscher (Quantitative Plant Biology, 2025)
Plants exhibit diverse morphological, anatomical and physiological responses to hypoxia stress from soil waterlogging, yet coordination between these responses is not fully understood. Here, we present a mechanistic model to simulate how rooting depth, root aerenchyma -porous tissue arising from localized cell death-, and root barriers to radial oxygen loss (ROL) interact to influence waterlogging survival. Our model revealed an interaction between rooting depth and the relative effectiveness of aerenchyma and ROL barriers for prolonging waterlogging survival. As the formation of shallow roots increases waterlogging survival time, the positive effect of aerenchyma becomes more apparent with increased rooting depth. While ROL barriers further increased survival in combination with aerenchyma in deep-rooted plants, ROL barriers had little positive effect in the absence of aerenchyma. Furthermore, as ROL barriers limit root-to-soil oxygen diffusion bidirectionally, our model revealed optimality in the timing of ROL formation. These findings highlight the importance of coordination between morphological and anatomical responses in waterlogging resilience of plants.